Analysis of different signal peptides for the secretory production of Ama r 2 in gram-positive systems (Lactococcus lactis). (January 2020) - Vasiee, Alireza; Norouzi, Neda; Yazdi, Farideh Tabatabaee; Mortazavi, Seyed Ali; Sankian, Mojtaba; Mahmoudi, Mahmoud; Shahidi, Fakhri
Abstract: Prokaryotic systems have been considered the most affordable and simplest hosts which are being employed to express recombinant proteins such as allergens; nevertheless, without appropriate signal peptide (SP), these systems cannot be used for secretory proteins. Recently, a lot of effort has been put into assessing the potential of gram-positive strains such as lactic acid bacteria for new applications in the production of heterologous proteins. Ama r 2 is a respiratory allergen from Amaranthus retroflexus, whose recombinant production in the probiotic host could be introduced as a specific and effective way to rapid diagnosis and immunotherapy of this allergy. Consequently, the production of this recombinant protein using the prokaryotic system, requires a suitable SP to protect disulfide bonds and to prevent misfolding. This study was designed to predict the best SPs for the expression of Ama r 2 protein in Lactococcus lactis as the host. In this study, 42 signal sequences were selected from SP databases and the most important features of them were evaluated. First, n, h and c regions of the SPs and their probabilities were investigated by signalP software version 4.1. Then, their physicochemical properties were evaluated by Portparam and SOLpro. Moreover, the secretion sorting and sub-cellular localization sites were evaluated by PRED-TAT and ProtcompB software programs. The results revealed that yjgB, entC2 (Entrotoxine type C-2), ent B (Entrotoxine type), blaZ (Beta lactamase), dex (number 21), blm (Beta lactamase 2), dex (Dextranase; number 20) and number 26 were introduced theatrically as the best SPs to express Ama r 2 in Lactococcus lactis . Highlights: Ama r 2 with a molecular weight of 14.2 kDa is one of the most allergic pollens in Iran. Designing the appropriate signal peptide is an important principle in the extracellular production of any protein. Our results introduced 8 signal peptides as the best candidate for extracellular Ama r 2 production.